No fluid overload in male ultra-runners during a 100 km ultra-run - Knechtle, B.; Senn, O.; Imoberdorf, R.; Joleska, I.; Wirth, A.; Knechtle, P.; Rosemann , T. (Research in Sports Medicine, 2011)
We investigated the change in body composition and hydration status in 27 male ultra-runners during a 100 km ultra-run. The athletes drank fluids ad libitum during the run; intake of calories, fluids, and electrolytes during performance were determined. Body mass decreased by 1.9 kg, haematocrit decreased, plasma [Na+] remained unchanged, and urinary specific gravity and plasma volume increased. Fluid intake was 0.52 (0.18) L/h and was related to running speed (r = 0.50; p = 0.0081). Delta body mass was associated with total fluid intake during the race (r = 0.49, p = 0.0095). Sodium intake amounted to 425 (478) mg/h and potassium intake to 140 (179) mg/h. Sodium and potassium intake were not related to either postrace concentration or change in plasma concentration. Sodium intake, however, was related to Delta urinary sodium concentration (r = 0.45, p = 0.0227). The increase in plasma volume was significantly and negatively related to both postrace plasma [Na+] (r = - 0.42, p = 0.0278) and the postrace potassium-to-sodium ratio in urine (r = - 0.44, p = 0.0218). To conclude, we found no fluid overload in these ultra-runners, the increase in plasma volume was most probably due to a stimulation of the renin-angiotensin-aldosterone system (RAAS) since sodium intake was not related to both the change in plasma [Na+] or postrace plasma [Na+].